Sorghum Yield Response to Water Supply and Irrigation Management - I. Kisekka; F. Lamm; A. Schlegel (Kansas Agricultural Experiment Station Research Reports, 2016)
Grain sorghum yield, under full and limited irrigation, was evaluated at three locations in western Kansas (Colby, Tribune, and Garden City). The top-end yield under full irrigation was 190 bu/a. However, there were no significant differences among irrigation treatments at all the three locations due to the above normal rainfall received during the 2015 growing season. These preliminary results indicate that there is potential to improve grain sorghum yields under limited irrigation. Additionally, best management practices to maximize kernels per head could have the greatest effect on grain yields.
Keywords: grain sorghum yield; full and limited irrigation; irrigation management; water supply; evapotranspiration; after boot